Cross-sectional study on the prevalence of contagious pathogens in bulk tank milk and their effects on somatic cell counts and milk yield - Alfonso Zecconi (Italian Journal of Animal Science, 2020)
Data on the prevalence of major contagious pathogens in bulk tank milk (BTM) in Italy are generally not available. The availability of Real-Time PCR procedures (qPCR) to perform BTM analysis by represents an important step to define herd health status. Therefore, a cross-sectional epidemiological study was designed to assess the prevalence of contagious pathogens and Prototheca spp in BTM samples. The study was performed on 581 herds from four districts in the west Lombardy region of Italy. Additionally, the relationship between pathogens in BTM and SCC or milk yield; the presence of an association between four risk factors (district, herd size, average milk yield and SCC) with pathogens in BTM were assessed. The overall data showed that S. aureus was recovered in 42% of the herds, Str. agalactiae in 10%, Prototheca spp in 11% and M. bovis in 1.5% of the herds. The GLM model applied showed a significant influence of BTM results, district, herd size and their interactions on SCC and on milk yield variance. Particularly, S. aureus or Str. agalactiae have a significant effect on milk yield variability and, in a lesser extent, on SCC. The very high prevalence of contagious pathogens significantly affects milk characteristics and yield, thus affecting economic sustainability of the herds, and suggests the need to implement control programmes to decrease the prevalence of contagious pathogens, This will also allow to decrease the use of antimicrobials and to improve cow welfare.Highlights First study on a large sample of Italian dairy herds on the prevalence of contagious pathogens in bulk tank milk samples. The prevalence value observed exceeded 50%. First study estimating the prevalence of M. bovis in bulk tank milk in a large sample of Italian dairy herds, and the prevalence observed was 1.5%. Prevalence of contagious pathogens has a significant influence on milk yield and SCC. Bulk tank milk SCC confirmed to have a low accuracy to identify infected herds.